Feminisme Dakwah Perempuan Dalam Film Habibie & Ainun 3 - Rinta Dwi Anggraini; Ahmad Nurcholis (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2021)
Feminism is suspected of being a women’s rebellious movement to deny the nature of being a woman and as a driving force to obtain women rights. Feminist ideology demands gender injustice. In preaching, men dominate the spread of Islam than women. Although the implementation of da’wah is predominantly male, there are also many da'iyah in Indonesia, one of which is Ainun. Gender differences do not make Ainun despair in achieving her dream as a doctor. So that this becomes unique to examine. This research uses qualitative methods with a feminist approach. The result of this study was the determine Ainun da’wah massage in the movie Habibie & Ainun 3, as well as the problems of Ainun as a da’iyah in Indonesia. Ainun can be used as an aspiration and role model for Indonesian people in education, concern, and desire to realize their dreams.